Changes in serum serotonin levels in patients with acute coronary syndrome and stable angina undergoing percutaneous coronary intervention. Issue 12 (December 2020) - Han, Donghoon; Choi, Jae Hyuk; Kim, Sehun; Park, Sang Min; Shin, Dong Geum; Kang, Min-Kyung; Choi, Seonghoon; Lee, Namho; Cho, Jung Rae
Objective: Activated platelets release serotonin, causing platelet aggregation and vasoconstriction. Serotonin levels were investigated in patients with acute coronary syndrome (ACS) and chronic stable angina (CSA) treated with percutaneous coronary intervention (PCI). Methods: Consecutive patients undergoing PCI for either ACS or CSA were enrolled between July 2009 and April 2010. Patients were pre-treated with dual antiplatelet agents (aspirin and clopidogrel) before PCI. Serum serotonin levels, measured at baseline, pre- and post-PCI, and at 90 min, and 6, 12, 24 and 48 h following PCI, were compared between ACS and CSA groups. Results: Sixty-three patients with ACS and 60 with CSA were included. Overall baseline characteristics were similar between the two groups. Serotonin levels at post-PCI (55.2 ± 120.0 versus 20.1 ± 24.0) and at peak (regardless of timepoint; 94.0 ± 170.9 versus 38.8 ± 72.3) were significantly higher in the ACS versus CSA group. At 90 min and 6, 24 and 48 h post-PCI, serum serotonin was numerically, but not significantly, higher in patients with ACS. Serotonin levels fluctuated in both groups, showing an initial rise and fall, rebound at 24 h and drop at 48 h post-PCI. Conclusions: In patients undergoing PCI, serum serotonin was more elevated in patients with ACS than those with CSA, suggesting the need for more potent and sustained platelet inhibition, particularly in patients with ACS.